STRENGTHENING BONDS, ENHANCING MIND: UNDERSTANDING THE IMPACT OF RELATIONSHIP QUALITY ON MENTAL WELL-BEING - Zohaib Rani; Dr. Abaid Ur Rehman; Dr. Malik Mureed Hussain; Shahbaz Ali Shahzad; Omar Farooq (International Journal of Contemporary Issues in Social Sciences, 2024)
This study aimed to understand the impact of relationship quality on mental well-being. Though various studies have demonstrated the importance of relationships between quality relationships and mental well-being, Pakistani culture is a classical or accustomed civilization where non-marital relationships between opposite genders are not acceptable. For this purpose, we recruited 136 participants through convenient with an age range of 18-40. Through convenient sampling technique data was collected from district Layyah with 53% undergraduate students, and 46.3% r were at master level. To measure the study variables, a relationship quality index and mental well-being questionnaire were adopted. Findings suggest that there is a significant role of quality relationships on mental well-being. The higher the levels of quality relationships, the higher the levels of mental well-being. The association between quality relationships and mental well-being was statistically significant. The study indicates a good relationship between couples has a positive impact on the mental well-being of both males and females. The study significantly contributes to a body of knowledge in the domain of mental health and it helps to understand the relationship.